1999
DOI: 10.1211/0022357991772493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicardipine on Collar-induced Intimal Thickening and Vascular Reactivity in the Rabbit

Abstract: The effects of nicardipine treatment on collar-induced intimal thickening and on accompanying reactivity changes in rabbit carotid artery have been investigated. Treatment for three weeks with subcutaneous nicardipine (20 mgkg(-1) per day) significantly inhibited the intimal thickening caused by perivascular application of a silicone rubber collar. Potassium chloride (KCl), phenylephrine and 5-hydroxytryptamine (5-HT) induced concentration-dependent contractions in both sham-operated and collared arteries. Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
5
14
0
Order By: Relevance
“…Morover, Geerts et al (2000) further reported that collar placement elevates mRNA expression and activity of the 5HT 1B receptor in the rabbit carotid artery. In our study, consistent with previous results (De Meyer et al 1994;Ü stu¨nes et al 1996;Kerry et al 1999;Yasa et al 1999), the collar placement suppressed 120 mM KCl-induced contractions in collared rabbit carotid arteries. In the collar model, attenuation of KCl-induced contractions is well known and has been discussed in detail (Kockx et al 1992;De Meyer et al 1994).…”
Section: Contractionsupporting
confidence: 93%
See 2 more Smart Citations
“…Morover, Geerts et al (2000) further reported that collar placement elevates mRNA expression and activity of the 5HT 1B receptor in the rabbit carotid artery. In our study, consistent with previous results (De Meyer et al 1994;Ü stu¨nes et al 1996;Kerry et al 1999;Yasa et al 1999), the collar placement suppressed 120 mM KCl-induced contractions in collared rabbit carotid arteries. In the collar model, attenuation of KCl-induced contractions is well known and has been discussed in detail (Kockx et al 1992;De Meyer et al 1994).…”
Section: Contractionsupporting
confidence: 93%
“…In accordance with the findings of previous studies (Ü stu¨nes et al 1996; Kerry et al 1999), collaring increased the pD 2 values of 5-HT in arteries, a characteristic feature of the collar model (De Meyer et al 1990Hickey et al 1996). As stated before, the 5-HT 1B receptor subtype has been found to be responsible for the development of hypersensitivity to 5-HT in the collar model (Geerts et al 1999(Geerts et al , 2000.…”
Section: Contractionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand NTG-induced vasorelaxation was not changed neither by collar (Fig. 5)- correlated with previous studies- (De Meyer et al, 1992, Kerry et al, 1999, Verbeuren et al, 1986, Yasa et al, 1999) nor by lacidipine. Based on these data we suggest that increased vasorelaxation to ACh by lacidipine was due to enhanced production of NO.…”
Section: Discussionsupporting
confidence: 92%
“…A similar hyperreactivity to 5‐HT develops when the rabbit carotid artery is surrounded by a flexible, silicone collar to induce intimal thickening ( De Meyer et al ., 1994 ) which is an essential prerequisite for the development of atherosclerosis in human arteries ( Stary et al ., 1995 ). Nevertheless the hypersensitivity to 5‐HT and the intimal hyperplasia are separate responses to the damage of the media ( De Meyer et al ., 1997 ) evoked by the collar ( De Meyer et al ., 1990 ; Kerry et al ., 1999 ; Van Put et al ., 1995 ; Üstünes et al ., 1996 ). According to clinical observations the concentration of platelet released products, including the vasoconstrictor agents 5‐HT and thromboxane A 2 (TXA 2 ), are significantly elevated in patients suffering from vasospasm ( van den Berg et al ., 1989 ; Vikenes et al ., 1999 ).…”
Section: Introductionmentioning
confidence: 99%